Prevalência de infecção pelo SARS-CoV-2 entre trabalhadores da limpeza urbana e manejo de resíduos sólidos durante a transmissão da variante Ômicron no Brasil - Santos, Fernanda Ferreira (2023)
COVID-19, a severe acute illness caused by the SARS-CoV-2 virus, was first detected in late 2019 in Wuhan, China. In Brazil, the first case was registered in 2020, when the WHO pandemic state was installed, with social isolation and a high number of hospitalizations. In view of this, some essential services were maintained, including urban cleaning workers, who constituted a vulnerable group, since they were responsible for handling solid waste and led them to be one of the groups with the highest occupational risk for SARS-CoV- 2, together with health professionals. In this perspective, the objective of this research was to evaluate the prevalence of infection by SARS-CoV-2 among urban cleaning workers during the transmission of the Omicron variant in Brazil through testing and a population questionnaire. This is a cross-sectional study carried out in the city of Aracaju, State of Sergipe, Northeastern Brazil, from February 1 to 8, 2022, and included urban cleaning and solid waste management workers who work in the city. The reverse transcriptase reaction test followed by polymerase chain reaction (RT-PCR) was used as a testing strategy and during the collection period, trained assistants collected nasal swabs, bilaterally, to perform the test. A total of 494 urban cleaning and solid waste management workers were included in the present study, 399 (80.8%) males and 95 (19.2%) females. The mean age was 39.1 years ± 11.7 years. Of the 494 workers evaluated, 111 (1/4; 95% CI 19.0–26.4) were positive for the presence of SARS-CoV-2 through testing and all were asymptomatic at the time of collection of data and biological material. Of the 111 positive cases of SARS-CoV-2 infection, 110 (1/4) occurred among individuals who received at least one dose of the COVID-19 vaccine and one case (1/5) among those who were not vaccinated. Furthermore, no differences were observed in the prevalence of infection according to the type of vaccine used and the vaccination status of workers. Thus, it was concluded that a small portion of the study workers reported not trusting the protective effect of the vaccine and precisely in this portion a higher prevalence of infection was detected, in addition to the prevalence in women and individuals under 40 years of age. The results indicate the need for better guidance on preventive measures against COVID-19 among urban cleaning and solid waste management workers.